The Transportation of Chinese Convicts from Hong Kong, 1844-1858 - Munn, Christopher (Journal of the Canadian Historical Association / Revue de la Société historique du Canada)

(untitled) (The Canadian Historical Association/La Société historique du Canada, 1997)
AbstractBetween 1844 and 1858 a total of 576 convicts, nearly all of them Chinese, were transported from Hong Kong to other British colonies. For the government this was a convenient, deterrent and inexpensive punishment in a jurisdiction troubled by high crime and low conviction rates. For the convicts the experience was a varied one: some served out long sentences with little prospect of return; others rebelled, escaped, or killed themselves. In 1858, when the last destination closed its doors to Hong Kong's transports, the colony was forced back on its own resources: with a prison dangerously overcrowded during a period of war and disorder, it faced a penal crisis similar to that experienced in England 75 years earlier. This article explores the policies, practices and experiences of transportation from early British Hong Kong and links the demise of transportation with controversial revisions of the colony's penal policies in the 1860s.